Inorganic silicon crystal heat insulation plate for smoke prevention and exhaust air pipe

By optimizing the process process and material ratio of inorganic silicon crystal insulation plates, a high -strength, low heat -conducting coefficient insulation board is formed, which solves the problem of unstable performance of existing heat insulation board in high temperature environments. Thermal insulation, mechanical strength and fire resistance.

CN119350051AActive Publication Date: 2025-01-24SHANGHAI SANJIAO WATER TECH INC

Patent Information

Application Number
CN202411477632.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing inorganic silicon crystal heat insulation boards have unstable performance in high-temperature environments, high thermal conductivity, insufficient compressive strength and poor fire resistance, which limits their application in high-temperature and high-pressure environments.

Method used

The composite materials such as high -purity silicon powder, alumina, mineral fiber and expansion perlite are used to optimize the process steps such as mixing, molding, drying, sintering and other processes to form a high -strength, low -heat conduction coefficient inorganic silicon insulation plate.

Benefits of technology

It significantly improves the thermal insulation effect, mechanical strength and fire resistance of the thermal insulation plate, avoiding the problem of surface coating and substrate peeling caused by steaming technology, and meets the high -performance heat insulation requirements in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350051A_ABST
    Figure CN119350051A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic silicon crystal heat insulation plate for a smoke prevention and exhaust air duct, which is prepared by the following steps: raw material treatment, mixing and stirring, forming, drying and curing, high-temperature sintering and surface treatment and inspection: after sintering is completed, the surface of the plate is ground to be flat, and rough and uneven parts on the surface are removed; and finally, performing quality inspection on heat conductivity coefficient, compressive strength and fire resistance. According to the invention, by optimizing the ratio of the silicon crystal powder to the aluminum oxide, the heat conduction loss can be effectively reduced, the structural integrity of the plate can be ensured when the plate bears external pressure, the plate is suitable for high-strength and long-term use industrial application environment, the service life of the product is prolonged, and the application value of the product in the field of fireproof safety is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat insulation board production, and specifically relates to an inorganic silicon crystal heat insulation board used for smoke exhaust air ducts. Background Art

[0002] Inorganic silicon crystal insulation board is a building material with excellent thermal insulation performance, widely used in fire prevention, smoke exhaust and other fields. Its production process usually involves the precise proportion of multiple raw materials and complex processing technology, including silicon crystal powder, alumina, mineral fiber and expanded perlite. These materials can effectively reduce heat conduction in high temperature environment, protect building structure and personnel safety.

[0003] However, inorganic insulation boards in the prior art often have problems such as high thermal conductivity, insufficient compressive strength and poor fire resistance, which limit their application in some high-temperature and high-pressure environments. In addition, the traditional production process has high requirements for the selection and processing of raw materials, which increases production costs and also leads to instability in product performance.

[0004] In the prior art, an inorganic silicon crystal material for smoke exhaust ducts and its preparation method (publication number CN113968713A) provides a more advanced "steam spray preheating pressing + autoclaving curing" preparation technology, which has higher heat transfer efficiency, uniform heating of the plate, short molding time, and its finished material is light and high-strength, has excellent fire resistance and anti-penetration properties, does not deform at high temperatures, and has a small linear expansion rate. However, due to the use of autoclaving technology in this technical solution, on the one hand, bubbles will be formed inside or on the surface of the material, affecting the appearance and performance. On the other hand, due to uneven temperature or pressure during use, the surface coating may be peeled off from the substrate.

[0005] Therefore, there is an urgent need for a new type of inorganic silicon crystal insulation board and its preparation method to improve the thermal insulation effect, mechanical strength and fire resistance of the material, while avoiding the autoclave technology that causes the surface coating and substrate to peel off, so as to meet the demand of the modern construction industry for high-performance insulation materials. Summary of the invention

[0006] The purpose of the present invention is to solve the problem that the existing thermal insulation materials have unstable performance and poor thermal insulation effect under high temperature environment, adopt high-purity silicon dioxide powder, alumina, mineral fiber and expanded perlite and other composite materials, and optimize the mixing, molding, drying, sintering and other process steps to form a high-strength, low thermal conductivity inorganic silicon crystal thermal insulation board, and provide an inorganic silicon crystal thermal insulation board for smoke exhaust duct.

[0007] The technical solution adopted by the present invention is as follows:

[0008] An inorganic silicon crystal heat insulation board for smoke exhaust duct includes the following steps:

[0009] ARaw material processing:

[0010] Mix high-purity silica powder with alumina and sieve to ensure uniform material fineness and control the particle size within the range of 40um-60um; Mineral fiber and expanded perlite are processed in advance to be free of impurities;

[0011] BMixing and stirring:

[0012] Add the processed silicon crystal powder and alumina mixture, mineral fiber and expanded perlite into the mixer in proportion and dry mix for 3-5 minutes;

[0013] Gradually add silicate binder during the mixing process and continue mixing for 5-8 minutes to ensure that the materials are evenly mixed and reach a consistency suitable for molding;

[0014] C Molding:

[0015] Place the mixed material in a pre-prepared mold and shape it by pressing / extrusion to ensure precise control of the thickness and size of the sheet;

[0016] D Drying and curing:

[0017] The formed insulation board needs to be dried at 80℃-100℃ for 12h-24h to remove moisture;

[0018] Then, the board is moved to a high temperature environment of 200℃-250℃ for curing, and the curing time is controlled within 3h-6h to ensure that the adhesive reacts thoroughly and forms a stable structure;

[0019] E High temperature sintering:

[0020] The board is sintered in a high-temperature kiln at 1200℃-1400℃ for 4h-6h. This step completely sintered the silicon crystal powder and the alumina skeleton to form an inorganic silicon crystal insulation board with high strength and low thermal conductivity.

[0021] FSurface treatment and inspection:

[0022] After sintering, the plate is ground to remove the rough and uneven surface.

[0023] Finally, quality inspections are carried out on thermal conductivity, compressive strength and fire resistance.

[0024] Wherein, in the raw material processing process described in step A, calculated by the total weight percentage after mixing, the proportion of silicon dioxide powder is 50%-70%, and the proportion of aluminum oxide is 30%-50%.

[0025] Wherein, in the mixing and stirring process described in step B, calculated by the total weight percentage after mixing, the ratio of the silica powder and the alumina mixture is 50%-70%, the ratio of the silicate binder is 15%-25%, the ratio of the mineral fiber is 10%-15%, and the ratio of the expanded perlite is 5%-10%.

[0026] Wherein, in the mixing and stirring process described in step B, the silicate binder is a mixture of one or more of sodium silicate, potassium silicate, lithium silicate and magnesium silicate;

[0027] Mineral fibers can be a mixture of one or more of rock wool fibers, glass fibers, ceramic fibers, and carbon fibers;

[0028] Expanded perlite is made by mixing an expander, an adhesive, an additive, perlite particle filler and water.

[0029] In the molding process described in step C, the mixture containing silicon crystal powder and aluminum oxide is physically compacted to form a strong three-dimensional network structure;

[0030] The hydration reaction of silicate binders, water molecules react with sodium silicate, potassium silicate, etc. to form gel-like silicates, making the particles more tightly bound;

[0031] Mineral fibers compress under pressure, forming a finer structure and enhancing thermal insulation performance;

[0032] The particles of expanded perlite squeeze each other under pressure and maintain their original shape, enhancing the structural strength;

[0033] Under high pressure conditions, the formation of tiny bubbles may cause some of the gas to escape, further enhancing the lightweight nature of the insulation board.

[0034] Wherein, the drying and curing process described in step D includes the following contents:

[0035] Water evaporation: the water in the board evaporates in a low temperature environment of 80℃-100℃ to form water vapor, which reduces the moisture content of the material and improves the dryness of the board;

[0036] The reaction of silicate adhesive. During the low-temperature drying process, the binding force between silicate adhesive and water is weakened, causing its hydrate to gradually lose water, which increases the hardness of the adhesive.

[0037] Cross-linking reaction: As the temperature rises, the silicon-oxygen bonds in the silicate adhesive gradually form a cross-linking structure, which improves the mechanical properties of the overall material;

[0038] Decomposition of organic matter: When there are organic additives in the mixture, thermal decomposition will occur under high temperature conditions to generate small molecular alkane, olefin and alkyne gases, carbon monoxide and hydrogen gas, further enhancing the fire resistance of the material;

[0039] Structural reorganization: During the high-temperature curing process, silicates interact with bauxite to form a more stable inorganic network structure, which improves the overall strength of the insulation board.

[0040] The high temperature sintering process described in step E specifically includes the following reactions:

[0041] Silicon crystal powder and alumina melt at a high temperature of 1200℃-1400℃ to form a liquid phase, which fills the gaps between the particles and promotes the bonding between the particles; the silicon-oxygen bonds and aluminum-oxygen bonds are reorganized to form a new stable inorganic silicon crystal network structure, which improves the strength and fire resistance of the material; some lightweight components are vaporized to reduce the weight of the material and improve the insulation effect; alumina undergoes a phase change to form a different crystal structure, which affects the thermal stability and mechanical properties of the material; the silicate binder reacts completely to form a highly cross-linked inorganic polymer network, which improves the overall strength and durability of the insulation board.

[0042] Among them, in the surface treatment and inspection process described in step F, specifically, a surface grinder / sand belt machine is used to grind the surface of the plate until the flatness is controlled within ±0.5mm and the surface roughness is less than 1.0um, thereby reducing heat conduction losses and improving thermal insulation performance.

[0043] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0044] 1. In the present invention, by optimizing the ratio of silicon crystal powder to alumina, the inorganic silicon crystal insulation board has excellent thermal conductivity, which can effectively reduce heat conduction loss, thereby greatly improving the insulation effect of the smoke exhaust duct and meeting the energy-saving needs in high temperature environments.

[0045] 2. In the present invention, by controlling the amount of expanded perlite and mineral fiber in different process steps, the compressive strength of the insulation board is significantly improved, ensuring that the board can maintain structural integrity when subjected to external pressure, and is suitable for high-strength, long-term use industrial application environments.

[0046] 3. In the present invention, a combined process of high-temperature sintering and surface treatment is adopted, which effectively improves the fire resistance of the insulation board, so that it can remain stable under fire or extreme high temperature conditions, which not only extends the service life of the product, but also further enhances its application value in the field of fire safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1It is a schematic diagram of the process of the present invention; DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0049] Embodiment 1, refer to Figure 1 , an inorganic silicon crystal insulation board for smoke exhaust duct, comprising the following steps:

[0050] ARaw material processing:

[0051] Mix high-purity silica powder with alumina and sieve to ensure uniform material fineness and control the particle size within the range of 45um±5um; process the mineral fiber and expanded perlite in advance to a state without impurities;

[0052] Calculated by the total weight percentage after mixing, the proportion of silicon dioxide powder is 50%, and the proportion of aluminum oxide is 50%.

[0053] BMixing and stirring:

[0054] Add the processed silicon crystal powder and alumina mixture, mineral fiber and expanded perlite into the mixer in proportion and dry mix for 3 minutes;

[0055] Gradually add silicate binder during the mixing process and continue mixing for 8 minutes to ensure that the materials are evenly mixed and reach a consistency suitable for molding;

[0056] Calculated by the total weight percentage after mixing, the proportion of the silicon dioxide powder and the aluminum oxide mixture is 50%, the proportion of the silicate binder is 25%, the proportion of the mineral fiber is 15%, and the proportion of the expanded perlite is 10%.

[0057] The silicate adhesive is sodium silicate; the mineral fiber can be rock wool fiber; and the expanded perlite is prepared by mixing an expansion agent, an adhesive, an additive, perlite particle filler and water.

[0058] C Molding:

[0059] Place the mixed material in a pre-prepared mold and shape it by pressing / extrusion to ensure precise control of the thickness and size of the sheet;

[0060] A mixture of silicon crystal powder and aluminum oxide is physically compacted to form a strong three-dimensional network structure;

[0061] The hydration reaction of silicate binders, water molecules react with sodium silicate, potassium silicate, etc. to form gel-like silicates, making the particles more tightly bound;

[0062] Mineral fibers compress under pressure, forming a finer structure and enhancing thermal insulation performance;

[0063] The particles of expanded perlite squeeze each other under pressure and maintain their original shape, enhancing the structural strength;

[0064] Under high pressure conditions, the formation of tiny bubbles may cause some of the gas to escape, further enhancing the lightweight nature of the insulation board.

[0065] D Drying and curing:

[0066] The formed insulation board needs to be dried at 80℃ for 24 hours to remove moisture.

[0067] Then, the board is moved to a high temperature environment of 200°C for curing for 3 hours to ensure that the adhesive reacts thoroughly and forms a stable structure.

[0068] Also included are the following:

[0069] Water evaporation: The water in the board evaporates at a low temperature of 80°C to form water vapor, which reduces the moisture content of the material and improves the dryness of the board.

[0070] The reaction of silicate adhesive. During the low-temperature drying process, the binding force between silicate adhesive and water is weakened, causing its hydrate to gradually lose water, which increases the hardness of the adhesive.

[0071] Cross-linking reaction: As the temperature rises, the silicon-oxygen bonds in the silicate adhesive gradually form a cross-linking structure, which improves the mechanical properties of the overall material;

[0072] Decomposition of organic matter: When there are organic additives in the mixture, thermal decomposition will occur under high temperature conditions to generate small molecular alkane, olefin and alkyne gases, carbon monoxide and hydrogen gas, further enhancing the fire resistance of the material;

[0073] Structural reorganization: During the high-temperature curing process, silicates interact with bauxite to form a more stable inorganic network structure, which improves the overall strength of the insulation board.

[0074] E High temperature sintering:

[0075] The board is sintered in a high-temperature kiln at 1200°C for 6 hours. This step completely sintered the silicon crystal powder and the alumina skeleton to form an inorganic silicon crystal insulation board with high strength and low thermal conductivity.

[0076] Specifically, the following reactions are included:

[0077] Silicon crystal powder and alumina melt at a high temperature of 1200℃ to form a liquid phase, which fills the gaps between particles and promotes the bonding between particles; the silicon-oxygen bonds and aluminum-oxygen bonds are reorganized to form a new stable inorganic silicon crystal network structure, which improves the strength and fire resistance of the material; some lightweight components are vaporized to reduce the weight of the material and improve the insulation effect; alumina undergoes a phase change to form a different crystal structure, which affects the thermal stability and mechanical properties of the material; the silicate binder reacts completely to form a highly cross-linked inorganic polymer network, which improves the overall strength and durability of the insulation board.

[0078] FSurface treatment and inspection:

[0079] After sintering, the plate is ground to remove the rough and uneven surface.

[0080] Finally, quality inspections of thermal conductivity, compressive strength, and fire resistance are conducted;

[0081] Specifically, a surface grinder / belt grinder is used to grind the surface of the plate until the flatness is controlled within ±0.5mm and the surface roughness is less than 1.0um, thereby reducing heat conduction loss and improving thermal insulation performance.

[0082] Example 2, refer to Figure 1 , an inorganic silicon crystal insulation board for smoke exhaust duct, comprising the following steps:

[0083] ARaw material processing:

[0084] Mix high-purity silica powder with alumina and sieve to ensure uniform material fineness and control the particle size within the range of 55um±5um; Mineral fiber and expanded perlite are processed in advance to be free of impurities;

[0085] Calculated by the total weight percentage after mixing, the proportion of silicon dioxide powder is 70%, and the proportion of aluminum oxide is 30%.

[0086] BMixing and stirring:

[0087] Add the processed silicon crystal powder and alumina mixture, mineral fiber and expanded perlite into the mixer in proportion and dry mix for 5 minutes;

[0088] Gradually add silicate binder during the mixing process and continue mixing for 5 minutes to ensure that the materials are evenly mixed and reach a consistency suitable for molding;

[0089] Calculated by the total weight percentage after mixing, the proportion of the silica powder and the alumina mixture is 70%, the proportion of the silicate binder is 15%, the proportion of the mineral fiber is 10%, and the proportion of the expanded perlite is 5%.

[0090] The silicate adhesive is sodium silicate; the mineral fiber can be rock wool fiber; and the expanded perlite is prepared by mixing an expansion agent, an adhesive, an additive, perlite particle filler and water.

[0091] C Molding:

[0092] Place the mixed material in a pre-prepared mold and shape it by pressing / extrusion to ensure precise control of the thickness and size of the sheet;

[0093] A mixture of silicon crystal powder and aluminum oxide is physically compacted to form a strong three-dimensional network structure;

[0094] The hydration reaction of silicate binders, water molecules react with sodium silicate, potassium silicate, etc. to form gel-like silicates, making the particles more tightly bound;

[0095] Mineral fibers compress under pressure, forming a finer structure and enhancing thermal insulation performance;

[0096] The particles of expanded perlite squeeze each other under pressure and maintain their original shape, enhancing the structural strength;

[0097] Under high pressure conditions, the formation of tiny bubbles may cause some of the gas to escape, further enhancing the lightweight nature of the insulation board.

[0098] D Drying and curing:

[0099] The formed insulation board needs to be dried at 100℃ for 12 hours to remove moisture.

[0100] Then, the board is moved to a high temperature environment of 250°C for curing for 3 hours to ensure that the adhesive reacts thoroughly and forms a stable structure.

[0101] Also included are the following:

[0102] Water evaporation: the water in the board evaporates at a low temperature of 100°C to form water vapor, which reduces the moisture content of the material and improves the dryness of the board;

[0103] The reaction of silicate adhesive. During the low-temperature drying process, the binding force between silicate adhesive and water is weakened, causing its hydrate to gradually lose water, which increases the hardness of the adhesive.

[0104] Cross-linking reaction: As the temperature rises, the silicon-oxygen bonds in the silicate adhesive gradually form a cross-linking structure, which improves the mechanical properties of the overall material;

[0105] Decomposition of organic matter: When there are organic additives in the mixture, thermal decomposition will occur under high temperature conditions to generate small molecular alkane, olefin and alkyne gases, carbon monoxide and hydrogen gas, further enhancing the fire resistance of the material;

[0106] Structural reorganization: during the high-temperature curing process, silicates interact with bauxite to form a more stable inorganic network structure, improving the overall strength of the insulation board.

[0107] E High temperature sintering:

[0108] The board is sintered in a high-temperature kiln at 1400°C for 4 hours. This step completely sintered the silicon crystal powder and the alumina skeleton to form an inorganic silicon crystal insulation board with high strength and low thermal conductivity.

[0109] Specifically, the following reactions are included:

[0110] Silicon crystal powder and alumina melt at a high temperature of 1400℃ to form a liquid phase, filling the gaps between particles and promoting the bonding between particles; the reorganization of silicon oxygen bonds and aluminum oxygen bonds forms a new stable inorganic silicon crystal network structure, which improves the strength and fire resistance of the material; the gasification of some lightweight components reduces the weight of the material and improves the insulation effect; the alumina undergoes a phase change to form a different crystal structure, which affects the thermal stability and mechanical properties of the material; the complete reaction of the silicate binder forms a highly cross-linked inorganic polymer network, which improves the overall strength and durability of the insulation board

[0111] FSurface treatment and inspection:

[0112] After sintering, the plate is ground to remove the rough and uneven surface.

[0113] Finally, quality inspections of thermal conductivity, compressive strength, and fire resistance are conducted;

[0114] Specifically, a surface grinder / belt grinder is used to grind the surface of the plate until the flatness is controlled within ±0.5mm and the surface roughness is less than 1.0um, thereby reducing heat conduction loss and improving thermal insulation performance.

[0115] Experimental example: By comparing the processing conditions of the heat insulation board obtained in Example 1 with those in Example 2, the following table 1 can be obtained:

[0116]

[0117]

[0118] Table 1, Comparison of treatment conditions of the heat insulation board obtained in Example 1 and Example 2

[0119] After testing the heat insulation boards obtained in Example 1 and Example 2, and comparing them with the existing conventional heat insulation board data, the following table 2 is obtained:

[0120]

[0121] Table 2, comparison of coefficients of the heat insulation boards obtained in Example 1 and Example 2 and conventional products

[0122] By comparison, we can observe the influence of different process conditions on the performance of inorganic silicon crystal insulation board, namely:

[0123] Thermal conductivity: The thermal conductivity of Example 2 is lower, showing better thermal insulation performance.

[0124] Compressive strength: The compressive strength of Example 2 is higher than that of Example 1 and conventional products, showing stronger mechanical properties.

[0125] Fire resistance: The fire resistance of Example 2 is the best, and can reach a fire resistance time of 6 hours.

[0126] In summary, in the above three groups of comparative data with significant advantages, due to the use of different raw material ratios and processing steps, the thermal conductivity, compressive strength and fire resistance of the inorganic silicon crystal insulation board have obvious differences. That is, in Example 2, after different material ratios and sintering treatments, the insulation board showed significantly better thermal conductivity, mechanical strength and fire resistance than the experimental group of the comparative example. Therefore, it can be considered that by optimizing the material composition and process flow, the inorganic silicon crystal insulation board can greatly improve its comprehensive performance in high temperature, load-bearing and safety protection.

[0127] On the other hand, the process in Example 2 not only improves the physical properties of the material, but also achieves a balance between durability and energy saving through reasonable raw material selection and processing steps, and is suitable for various application scenarios such as construction and industrial smoke exhaust ducts.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An inorganic silicon crystal insulation board for smoke exhaust duct, characterized in that: The following steps are involved: ARaw material processing: Mix high-purity silica powder with alumina and sieve to ensure uniform material fineness and control the particle size within the range of 40um-60um; Mineral fiber and expanded perlite are processed in advance to be free of impurities; BMixing and stirring: Add the processed silicon crystal powder and alumina mixture, mineral fiber and expanded perlite into the mixer in proportion and dry mix for 3-5 minutes; Gradually add silicate binder during the mixing process and continue mixing for 5-8 minutes to ensure that the materials are evenly mixed and reach a consistency suitable for molding; C Molding: Place the mixed material in a pre-prepared mold and shape it by pressing / extrusion to ensure precise control of the thickness and size of the sheet; D Drying and curing: The formed insulation board needs to be dried at 80℃-100℃ for 12h-24h to remove moisture; Then, the board is moved to a high temperature environment of 200℃-250℃ for curing, and the curing time is controlled within 3h-6h to ensure that the adhesive reacts thoroughly and forms a stable structure; E High temperature sintering: The board is sintered in a high-temperature kiln at 1200℃-1400℃ for 4h-6h. This step completely sintered the silicon crystal powder and the alumina skeleton to form an inorganic silicon crystal insulation board with high strength and low thermal conductivity. FSurface treatment and inspection: After sintering, the plate is ground to remove the rough and uneven surface. Finally, quality inspections are carried out on thermal conductivity, compressive strength and fire resistance.

2. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 1, characterized in that: In the raw material processing process described in step A, the proportion of silicon dioxide powder is 50%-70%, and the proportion of aluminum oxide is 30%-50%, calculated by the total weight percentage after mixing.

3. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 2, characterized in that: In the mixing and stirring process described in step B, calculated by the total weight percentage after mixing, the ratio of the silica powder and the alumina mixture is 50%-70%, the ratio of the silicate binder is 15%-25%, the ratio of the mineral fiber is 10%-15%, and the ratio of the expanded perlite is 5%-10%.

4. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 3, characterized in that: In the mixing and stirring process described in step B, the silicate binder is a mixture of one or more of sodium silicate, potassium silicate, lithium silicate and magnesium silicate; Mineral fiber can be a mixture of one or more of rock wool fiber, glass fiber, ceramic fiber and carbon fiber; Expanded perlite is made by mixing an expander, an adhesive, an additive, perlite particle filler and water.

5. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 1, characterized in that: In the molding process described in step C, the mixture containing silicon crystal powder and aluminum oxide is physically compacted to form a strong three-dimensional network structure; The hydration reaction of silicate binders, water molecules react with sodium silicate, potassium silicate, etc. to form gel-like silicates, making the particles more tightly bound; Mineral fibers compress under pressure, forming a finer structure and enhancing thermal insulation performance; The particles of expanded perlite squeeze each other under pressure and maintain their original shape, enhancing the structural strength; Under high pressure conditions, the formation of tiny bubbles may cause some of the gas to escape, further enhancing the lightweight nature of the insulation.

6. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 1, characterized in that: The drying and curing process described in step D includes the following: Water evaporation: the water in the board evaporates in a low temperature environment of 80℃-100℃ to form water vapor, which reduces the moisture content of the material and improves the dryness of the board; The reaction of silicate adhesive. During the low-temperature drying process, the binding force between silicate adhesive and water is weakened, causing its hydrate to gradually lose water, which increases the hardness of the adhesive. Cross-linking reaction: As the temperature rises, the silicon-oxygen bonds in the silicate adhesive gradually form a cross-linking structure, which improves the mechanical properties of the overall material; Decomposition of organic matter: When there are organic additives in the mixture, thermal decomposition will occur under high temperature conditions to generate small molecular alkane, olefin and alkyne gases, carbon monoxide and hydrogen gas, further enhancing the fire resistance of the material; Structural reorganization: During the high-temperature curing process, silicates interact with bauxite to form a more stable inorganic network structure, which improves the overall strength of the insulation board.

7. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 1, characterized in that: The high temperature sintering process described in step E specifically includes the following reactions: Silicon crystal powder and alumina melt at a high temperature of 1200℃-1400℃ to form a liquid phase, which fills the gaps between the particles and promotes the bonding between the particles; the silicon-oxygen bonds and aluminum-oxygen bonds are reorganized to form a new stable inorganic silicon crystal network structure, which improves the strength and fire resistance of the material; some lightweight components are vaporized to reduce the weight of the material and improve the insulation effect; alumina undergoes a phase change to form a different crystal structure, which affects the thermal stability and mechanical properties of the material; the silicate binder reacts completely to form a highly cross-linked inorganic polymer network, which improves the overall strength and durability of the insulation board.

8. The inorganic silicon crystal heat insulation board for smoke exhaust duct according to claim 1, characterized in that: In the surface treatment and inspection process described in step F, a surface grinder / sand belt machine is specifically used to grind the surface of the plate to a flatness within ±0.5 mm and a surface roughness below 1.0 um, thereby reducing heat conduction losses and improving thermal insulation performance.

Citation Information

Patent Citations

  • Nano-composite heat insulation plate and preparation method thereof

    CN110655379A

  • Rock wool fiber-reinforced silicon oxide-based high-strength thermal-insulation composite material and preparation method thereof

    CN111454071A

  • Inorganic silicon crystal material for smoke prevention and exhaust air pipe and preparation method thereof

    CN113968713A

  • Inorganic silicon crystal smoke prevention and exhaust air pipe and manufacturing method thereof

    CN114135724A

  • Inorganic silicon crystal plate and manufacturing method thereof

    CN114195432A

Cited By

  • Inorganic silicon crystal fireproof thermal insulation material for fireproof air duct and preparation method of inorganic silicon crystal fireproof thermal insulation material

    CN121318360A